Perceived safety culture of healthcare providers in selected public and private hospitals in Tacloban City - Jabonete, Fritz Gerald V.
Safety culture has been proposed as a means to keep patients safe. Thus, identifying the level of culture and awareness on patient safety is essential in order to improve the quality of care. This study aimed to determine the perceived safety culture of healthcare providers in selected institutions in Tacloban City. This study utilized the Manchester Patient Safety Culture Assessment Tool. The tool consisted of 10 dimensions to reflect the entire safety culture. A descriptive-correlation, comparative design was used in this study. -- Generally, healthcare providers in the private hospitals have higher level of safety maturity as compared to those in the public hospitals. Most healthcare personnel perceived learning and effecting change, personnel management, and staff education and training at a proactive level. They also perceived that hospitals have a punitive response to error reports. Overall scores on the perception of safety culture showed that auxiliaries (49.4%) obtained the highest score at a proactive level. Study findings will guide hospital leaders to give focus on strategies to improve patient safety. This study also suggests that group-specific interventions should be campaigned to improve patient safety.